Association of blood trihalomethane concentrations with diabetes mellitus in older adults in the US: a cross-sectional study of NHANES 2013–2018 - Chen, Tuotuo; He, Haiqing; Tang, Wei; Liu, Ziyi; Zhang, Hongliang (Frontiers in Endocrinology, 2024)
Previous studies have demonstrated that there is a correlation between trihalomethanes and the dis-eases progression, such as allergic diseases. As we know, only few studies focused on the relation-ship between trihalomethanes and metabolic diseases, such as diabetes mellitus. Data were collected from NHANES database in the survey cycle during 2013 to 2018, including 2,511 the American elderly whose blood trihalomethane concentrations were measured, involving chloroform (TCM)and brominated trihalomethanes (Br-THMs). Brominated trihalomethanes include bromodichloromethane (BDCM), dibromochloromethane (DBCM), bromoform (TBM). Meanwhile, the concentration of total trihalomethanes (TTHMs) was also measured later. A multi-variate logistic regression and restricted cubic spline were used to examine the relationship between blood THMs and diabetes mellitus.Meanwhile, we performed a subgroup analysis, which was to explore the stability of this relationship in different subgroups. In order to further consider the im-pact of various disinfection by-products on diabetes, we also used Weighted quantile sum (WQS). To explore the correlation in trihalomethanes, we plot a correlation heatmap.Adjusting for potential confounders, we found that there was a significant negative association be-tween chloroform and diabetes mellitus [Model 1(adjusted for covariates include age, sex, and race, OR=0.71;95% CI:0.50 -1.02; P=0.068; P for trend=0.094) Model 2(adjusted for all covariates OR=0.68;95% CI:0.48–0.96; P=0.029; P for trend=0.061)]. In the bromodichloromethane, we found the conclusion that is similar to TCM [Model 1(adjusted for covariates include age, sex, and race, OR=0.54;95% CI:0.35 -0.82; P=0.005; P for trend=0.002), Model 2(adjusted for all covariates OR=0.54;95% CI:0.35–0.82; P=0.003; P for trend=0.002)]. Meanwhile, the restricted cubic spline curve also further confirms this result (P overall= 0.0027; P overall<0.001). Based on the analysis in the subgroups, we found that the value P for interaction in majority subgroups is more than 0.1. Trihalomethanes and diabetes were inversely associated, and in the WQS, chloroform and bromodichloromethane were found to be the major contributors to this relationship. In the correlation analysis, we found that most trihalomethanes have a weak correlation, except for TBM and TCM with a strong correlation. Our results in this study showed that blood chloroform, bromodichloromethane concentrations, and diabetes mellitus in the U.S elderly are negatively correlated